Australian superannuation (pension) fund product ratings and performance: A guide for fund managers. (May 2016) - Watson, John; Delaney, James; Dempsey, Michael; Wickramanayake, J.
This paper investigates the ability of Morningstar superannuation fund ratings to predict future performance in the context of the Australian superannuation fund industry. In this context, we make provisions for fund size and fund age. We draw three broad conclusions. First, fund ratings can assist in predicting funds that are likely to significantly underperform in subsequent periods. Second, the ratings are mostly unable to distinguish between highly and moderately performing funds. Third, the likelihood of a fund being highly rated is negatively related to the size of assets under management and positively related to its age. Accordingly, the paper should be of benefit not only to fund managers seeking to identify underperforming funds, but also to fund advisers, retail investors, and trustee boards choosing SF products for investment choice menus.